Protective Effect of Tartaty Buckwheat Extract Fermented with Pleurotus eryngii on Alcoholic Liver and Stomach Injury in Mice - Yuqi MA; Mei WANG; Xiaonian CAO; Qiang LI; Dingtao WU; Ling DONG; Fengju ZHANG; Yichen HU (Shipin gongye ke-ji, 2024)
Objective: To investigate the antioxidant activity of fermented tartaty buckwheat extract of Pleurotus eryngii in vitro as well as its protective effect on alcohol-induced liver and gastric mucosa injury in vivo. Methods: The study involved determining the contents of functional components in fermented tartary buckwheat extract and observing its antioxidant capacity. Mice models of chronic alcoholic liver and gastric mucosa injury were established using Lieber-DeCarli liquid feed. The protective effects of fermented tartary buckwheat extract at low and high doses (1.5 g/kg B.W., 3.0 g/kg B.W.) were investigated for both liver and gastric mucosa injury. Results: The extract of fermented buckwheat with Pleurotus eryngii contained more antioxidant components, the contents of polyphenols, flavonoids and triterpenes were 11.40±0.32 mgGAE/g DW, 17.19±0.30 mg RE/g DW and 7.59±0.24 mg/g, respectively. The contents of rutin and quercetin were as follows: 13.55±0.05 and 0.665±0.01 mg/g. The iron reducing antioxidant capacity and DPPH and ABTS+ free radical scavenging efficiency of Tartary buckwheat extract were 16.66±0.65, 33.49±1.26 and 15.68±1.17 μmol Trolox/g DW, respectively. Compared with the model group, both high-dose and low-dose groups significantly reduced malondialdehyde (P<0.05), aspartate aminotransferase (P<0.01), alanine aminotransferase (P<0.01), lactate dehydrogenase (P<0.05), and interleukin-1β (P<0.05) levels and significantly increased levels of superoxide dismutase (P<0.01) and glutathione peroxidase (P<0.01), downregulated protein expression levels of reactive oxygen species (P<0.01), rat sarcoma (P<0.01), rapidly accelerated fibrosarcoma (P<0.01), extracellular signal-regulated kinases (P<0.05), and mitogen activated protein kinase kinase (P<0.05). Conclusion: Fermented tartaty buckwheat extract of Pleurotus eryngii has good antioxidant activity, and has obvious protective effect on chronic alcoholic liver and gastric mucosa injury in mice.